2013
DOI: 10.1002/jgrb.50245
|View full text |Cite
|
Sign up to set email alerts
|

Rapid postseismic relaxation after the great 2006–2007 Kuril earthquakes from GPS observations in 2007–2011

Abstract: The 2006–2007 doublet of Mw > 8 earthquakes in the Kuril subduction zone caused postseismic transient motion in the asthenosphere, which we observed on the Kuril GPS Array in 2007–2011. Here we show that the Maxwell asthenospheric viscosity that best fits the geodetic data increased by nearly an order of magnitude over the interval of 4 years, from 2 × 1017 to 1 × 1018 Pa s. These effective values of viscosity can be explained by a power law rheology for which strain rate is proportional to stress raised to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
4

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 45 publications
2
22
1
4
Order By: Relevance
“…Kogan et al . [, ] presented a postseismic uplift rate up to 1.2 cm/yr (KURILNET site MATC) from near‐field GPS stations along the volcanic arc, which confirmed that the postseismic deformation is caused predominantly by viscoelastic relaxation (rather than afterslip). We henceforth assume that the GRACE gravity changes are shaped primarily by viscoelastic relaxation and ignore the possible contribution of afterslip.…”
Section: Grace Observation Of Postseismic Gravity Changementioning
confidence: 70%
See 1 more Smart Citation
“…Kogan et al . [, ] presented a postseismic uplift rate up to 1.2 cm/yr (KURILNET site MATC) from near‐field GPS stations along the volcanic arc, which confirmed that the postseismic deformation is caused predominantly by viscoelastic relaxation (rather than afterslip). We henceforth assume that the GRACE gravity changes are shaped primarily by viscoelastic relaxation and ignore the possible contribution of afterslip.…”
Section: Grace Observation Of Postseismic Gravity Changementioning
confidence: 70%
“…We will present the details of GRACE observations and viscoelastic modeling results with a range of rheological parameters (thickness of lithosphere and asthenosphere viscosity) and of coseismic moment magnitude ratios and compare with the previous Kuril GPS studies of Kogan et al . [, ].…”
Section: Introductionmentioning
confidence: 99%
“…This process has been explained in the context of the velocity strengthening behavior24, and has been observed mainly in the down-dip region of megathrust-earthquakes2526. At longer time scales, post-seismic deformation can be modeled as viscoelastic relaxation of the subducted slab, underlying asthenosphere and overlying asthenospheric mantle wedge232728. Viscoelastic relaxation models predict post-seismic deformation observed for several years or decades after the earthquake, including subsidence over the down-dip limit of co-seismic slip and on the rupture area and uplift seaward29.…”
Section: Discussionmentioning
confidence: 99%
“…[] for the 2004 Sumatra earthquake and Kogan et al . [] for the 2006 Kuril earthquake. Both of their geographical settings are also along the subduction trenches, similar to that for the Tohoku‐Oki event, so they are expected to provide approximate interpretation for the present observations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, such postseismic phenomena after large earthquakes are in some cases discussed with another transient process, specifically, viscoelastic relaxation of stress induced by the coseismic slip in the upper mantle [e.g., Wang et al ., ]. Several researches have performed evaluation of viscoelastic responses following megathrust earthquakes for several years together with the afterslip, e.g., for the 2004 Sumatra earthquake [ Pollitz et al ., ; Hu and Wang , ] and the 2006–2007 Kuril earthquakes [ Kogan et al ., ]. However, they used only terrestrial geodetic data, which are insufficient to resolve the deformation beneath the ocean [e.g., Loveless and Meade , ].…”
Section: Introductionmentioning
confidence: 99%